The significance of the subject in contemporary Iraqi sculpture (beginnings) (Journal of the College of Basic Education, 2022)
To begin with, it can be said that most of the human artistic productions since ancient times and in all its subjects had their indications and their various stages of time, and when we delve into the midst of these productions, we will inevitably find many of these artistic subjects that we find in their meanings a true expression of the reality of social, political and intellectual life. Philosophy for a specific period of time, and representative of a specific society, that this process cannot achieve success unless there are individual artists from that society who are responsible for formulating and crystallizing artistic topics, to express the social reality and translate it in the form of works that clarify the state of society for a certain era.Through our research, we will shed light through study and analysis on the work of a group of sculptors, who were chosen according to their representation of the artistic stage of that social reality, and we can even consider them an integral part of that reality. The stage that we are dealing with here can be considered the stage of the beginnings of contemporary Iraqi sculpture, which included the meanings and indications of many topics that expressed the reality of the stage with a modern spirit and vision.The research in the significance of the subject in contemporary Iraqi sculpture is an attempt to reveal sculptural topics completed at a specific stage by Iraqi sculptors who have pioneered the establishment of the contemporary Iraqi sculpture art movement, except for the sculptor Jawad Salim, after his travel outside Iraq and his return from his studies in Europe in the thirties and forties of the century Al-Munasrim, the sculptor Khaled Al-Rahal, and the sculptor Muhammad Ghani Hikmat. These sculptors were destined to have the greatest role in laying the foundation stone for the beginning of contemporary Iraqi sculpture.